O nascimento da obesidade: um estudo genealógico do discurso patologizante - Santolin, Cezar Barbosa (2012)
This study aimed to investigate the historical emergence of obesity´s pathologizing discourse in the West. The methodology used was the analysis of discourse from the perspective of archaeo-genealogy of Michel Foucault. According to the consulted sources, the hypothesis suggested by some historians that there was a pathologizing discourse of obesity equivalent of nowadays in Pre-history, the Antiquity, in the Middle Ages and in the Renaissance was refuted. It was concluded that such claims result from a retrospective conceptual projections in analysis of historical sources, as well as questionable inferences. The evidence found suggest that the pathologization of excessive body size and/or body fat would have occurred in the mid-seventeenth century and it has remained a marginal concern until the midnineteenth century, when it became popular. During this period, named the birth of obesity, it was found aesthetic, moral, religious, political and gender influences in medical discourses through the obesity´s pathologization process. The research also allowed to notice the presence of a discoursive dissonance that would derail a linear and homogeneous history narration, as some historians draw up. In addition, research may show that the comedy, the stigma and the ridiculing were among the strategies used to pathologizing the condition, including by medicine. Finally, the research allowed to describe how discoursive agents legitimized the constitution of a biological ideal based on the concept of normality, as how the concept of risk supports the pathologizing discourse until today and how it legitimizes the exercise of normalizing biopower